Smart aquaculture system: internet of things-based contextual e-service for sustainable aquafarming - Md Abdullah Al Rahib; Md Redwan Hussain; Md. Zubayer Chowdhury; Jarin Tias Meraj; Abdus Sattar (Institute of Advanced Engineering and Science, 2026)
A creative and contextual e-service for aquaculture system is developed to handle threats that climate change poses to global ecology and sustainable aquaculture. Therefore,